P9. Correlation of radiation induced apoptosis with Bax and Bcl-2 protein expression. (September 2016) - Sogwagwa, N.; Davison, G.; Khan, S.; Solomon, W.
Abstract : Introduction: Apoptosis is cell death induced by radiation and is the key mechanism used to remove cells with significant DNA damage. Apoptosis is controlled by the Bcl-2 family proteins and therefore the balance between Bax and Bcl-2 expression is important. The objectives of this study were to evaluate the effect of ionising radiation on these apoptotic proteins, and to explore if there is a relationship between radiation induced apoptosis (RIA) and Bcl-2 or Bax expression. Materials and methods: In an effort to study individual's sensitivity to radiation, blood from 25 healthy donors was exposed to radiation (0 Gy, 2 Gy, 8 Gy). After 48 h RIA was estimated on CD4 and CD8 lymphocytes using the LAA. Isolated lymphocytes were also analysed for Bcl-2 and Bax protein expression using Western Blot analysis. Statistical analysis was performed to determine if there was a difference in expression between the three doses of radiation and if a relationship existed between RIA and Bcl-2 and Bax expression. Results: Analysis of the CD4 lymphocytes demonstrated a higher RIA after 8 Gy radiation when compared to 2 Gy (10.22% (7.12–18.42%)); 3.00% (1.02–6.10%) P < 0.0001). CD8+ lymphocytes also had significantly higher RIA after 8 Gy when compared to 2 Gy, (27.59% (16.98–37.63%); 8.88% (4.45–12.87%) P < 0.0001).There was a significant difference in Bax expression between 0 Gy and 8 Gy ( P = 0.0361), and a near significant difference between 2 Gy and 8 Gy ( P = 0.0924). However no significant difference was detected between 0 Gy and 2 Gy or in the expression of Bcl-2 between 0 Gy, 2 Gy and 8 Gy. Conclusion: Both lymphocytes demonstrated a dose dependent increase in apoptotic response. This is accompanied by an increase in Bax (pro-apoptotic) expression and no significant difference in the expression of the apoptotic (anti-apoptotic) Bcl-2. Further analysis should aim at comparing expression of donors with high radiosensitivity with low sensitivity and the investigation of other proteins within the apoptotic pathway.